2014
DOI: 10.9790/3008-095492106
|View full text |Cite
|
Sign up to set email alerts
|

The impact of each of the essential oils of marjoram and lemon grass in conjunction with gamma irradiation against the Greater Wax Moth, Galleria Mellonella

Abstract: (100,150,200,250 and 300 Gy) and the combined effect of them and essential oil were tested. Results: Comparing the estimated LC10, LC50, LC90 values of present investigation of mentioned essential oils indicated that essential oils of Origanum majorana is more toxic to G. mellonella than the other essential oil of Cymbopogon proximus, then were selected in combined with the dose of 100 Gy in the shared experience. It also found that the percentage of pupation, emergence and sex ratio decreased with increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Data listed in Table (3) clearly revealed that the PLs population gradually decreased in haemolymph with the larval instar (9.6±0.5 and 8.8±0.4 cells/mm 3 , in 5 th and 7 th instars, respectively). After treatment of 3 rd instar larvae with LC 50 of each of the venoms, data of disturbance in PLs population had been assorted in the same table.…”
Section: Fluctuated Pls Populationmentioning
confidence: 94%
See 1 more Smart Citation
“…Data listed in Table (3) clearly revealed that the PLs population gradually decreased in haemolymph with the larval instar (9.6±0.5 and 8.8±0.4 cells/mm 3 , in 5 th and 7 th instars, respectively). After treatment of 3 rd instar larvae with LC 50 of each of the venoms, data of disturbance in PLs population had been assorted in the same table.…”
Section: Fluctuated Pls Populationmentioning
confidence: 94%
“…The greater wax moth Galleria mellonella (Linnaeus) (Lepidoptera: Pyralidae) is widely distributed throughout the world. Although the adults do not feed, because they have atrophied mouth parts, the voracious nature of larval feeding and tunneling lead to the destruction of the honeycomb, and subsequently to the death of weak colonies [1][2][3][4]. For the control of G. mellonella, various physical methods have been adopted; including freezing, heating, CO 2 , Ozone gas and sulphur fumigation against larvae and pupae [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Gamma rays act as a substance capable of inducing mutation, it passes over the tissues and damage cell's nucleus (Morales-Ramirez et al, 1997;World of Microbiology and Immunology, 2003). It is evident that gamma radiation affects normal growth, development, and reproduction of insects (Hallman, 2003;Helinski et al, 2009;Kheirallah, 2016;Kheirallah et al, 2017) and may cause either sterility or mortality (Prabhakumary et al, 2011;Sengupta, 2013;Mohamed et al, 2014). A paucity of investigations reported the effect of gamma radiation on the histological and ultrastructure of insects (Paoli et al, 2014;Kheirallah 2016;Hassan et al, 2017;Kheirallah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A novel trend is being oriented to biological control methods such as sterile insect techniques (SIT) [6] through exposing the insects to irradiation at doses adequately enough to induce the favorite effects and release in the field to suppress the population. This technique is applied to control insect pests by generating sterility, inducing a disturbance in biochemical metabolism or mortality of the insects [8, 22,19,30,4]. The efficiency of gamma irradiation is wide-ranging between different insect orders and age-related to the same species [26].…”
Section: Introductionmentioning
confidence: 99%